Image Branding Management in Increasing Competitiveness of Raudlatul Athfal in The Society 5.0 Era - Latifatus Saleha; Lutfiatul Iltiqaiyyah; Chodijatus Sholihah (Yayasan Avicenna, 2022)
This study aims to determine the increase in the competitiveness of raudlatul athfal involving branding image management in the era of society 5.0. This is qualitative research with a case study conducted at Raudlatul Athfal Perwanida III in a Probolinggo district. The sources of informants in this study were school principals, curriculum, public relations, teachers, and student guardians. Then to select and determine the informants in this study, researchers used a purposive sampling technique. Data collection techniques in this study used content/document analysis techniques, in-depth interviews, and events/observations. The method used to check the validity of the data is the triangulation method. The data analysis technique used in this research is interactive model analysis. The stages in analyzing the data in this study are data reduction, data presentation, and conclusion. The results in this study indicate that first, Raudlatul Athfal Perwanida III involves branding image management in increasing Raudlatul Athfal's competitiveness in the era of society 5.0. Second, the control of the branding image management strategy is carried out using; Problem Mapping, Implementation of Branding Image, Result Branding Image and Continous Improvement. The implications obtained by carrying out branding image management can increase public confidence in choosing Raudlatul Athfal Perwanida III as an institution capable of educating the nation's next generation. the control of the branding image management strategy is carried out using; Problem Mapping, Implementation of Branding Image, Result Branding Image and Continous Improvement. The implications obtained by carrying out branding image management can increase public confidence in choosing Raudlatul Athfal Perwanida III as an institution capable of educating the nation's next generation. the control of the branding image management strategy is carried out using; Problem Mapping, Implementation of Branding Image, Result Branding Image and Continous Improvement. The implications obtained by carrying out branding image management can increase public confidence in choosing Raudlatul Athfal Perwanida III as an institution capable of educating the nation's next generation.